2002
DOI: 10.1385/endo:18:3:207
|View full text |Cite
|
Sign up to set email alerts
|

Gingival Enlargement in Acromegaly

Abstract: In this study, we investigated gingival enlargement in patients with acromegaly as a component of the disease. Eleven patients (5 males, 6 females) were evaluated. Diagnosis was confirmed with typical clinical features and laboratory. Oral examinations were carried out by the same periodontist. During the examination, plaque index, gingival index, probing pocket depths, and gingival enlargement values were evaluated. Duration of the disease was between 0.2 and 13 yr. Seven patients had pituitary macroadenomas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…Although GH excess has complex consequences on bone and connective tissue metabolism there is yet very few data about periodontal pathologies in these patients (25)(26)(27). As long as our English literature search is concerned, we could fi nd only one study evaluating the periodontal status in acromegalics.…”
Section: Tab 4 Chronic Periodontitis Cases In Acromegalicsmentioning
confidence: 99%
“…Although GH excess has complex consequences on bone and connective tissue metabolism there is yet very few data about periodontal pathologies in these patients (25)(26)(27). As long as our English literature search is concerned, we could fi nd only one study evaluating the periodontal status in acromegalics.…”
Section: Tab 4 Chronic Periodontitis Cases In Acromegalicsmentioning
confidence: 99%
“…There is a clinical report of gingival hypertrophy in 8 of 11 acromegaly patients whose blood GH levels were controlled. 1 It was also reported that local injection of small doses of The Endocrinologist • Volume 17, Number 1, February 2007 Gingivitis in Acromegaly somatotrophic hormone into the oral mucosa of young adult rats causes enlargement of epithelial cells. 5 The gingivitis was not improved until a GH secretion inhibitor was administered; this suggests that the acromegaly induced enlargement of the gingiva.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we found no case of diffuse gingival hypertrophy (only one case of bilateral palatal tuberous outgrowth). One study described mild to moderate gingival ‘enlargement’ in 8 acromegalic patients out of 11 examined ( 8 ) but it was not reported if this term means thick gingival biotype or gingival hypertrophy and if periodontitis was associated. In the same way, although there is preclinical evidence of a trophic role of acromegaly on cementum ( 25 ) and two published cases reports mentioning radiological hypercementosis on molars of acromegalic patients ( 12 , 13 ), systematic orthopantomogram revealed only two cases of hypercementosis, each affecting only one tooth per patient.…”
Section: Discussionmentioning
confidence: 99%
“…A total score below 80 points, that is, 66% is considered as a clinically significant impact of acromegaly on patients' quality of life. This score can be divided into three dimensions: Physical Symptoms subscale (i.e., Items 1,3,9,[13][14][15]19, and 22), Appearance Issues subscale (i.e., Items 2,4,7,11,12,16,and 17), and Personal Relation Issues subscale ( Items 5,6,8,10,18,20 and 21). As for the global score, results for each dimension were scored on a 0 to 100 basis.…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation